Π‐Excess Aromatic σ2P Ligands: Formation of a Heterocyclic 1, 2‐Diphosphine by the Addition of tBuLi and Subsequent Inverse Addition of the Product at the P=C Bonds of Two Molecules of 1‐Neopentyl‐1, 3‐benzazaphosphole. Issue 6 (29th June 2015) - Aluri, Bhaskar R.; Ghalib, Mohammed; Kindermann, Markus K.; Jones, Peter G.; Heinicke, Joachim W.
ABSTRACT: The reactivity of t BuLi (pentane) toward the N‐neopentyl‐substituted π‐excess P=CH–N heterocycle1 depends on the solvent (tetrahydrofuran, diethyl ether, hexane, and toluene) and reaction conditions. Trapping of the resulting organolithium compounds with CO2 /ClSiMe3, ClSiMe3, or EtI led to various products indicating CH lithiation (1a, b ), normal addition of t BuLi at the P=C bond ( E/Z ‐2a, b ), inverse addition of the primary addition product2Li at the P=C bond of a second molecule1, affording 3‐ tert ‐butyl‐2, 2'‐bis(1, 3‐benzazaphospholines)3, or inverse addition of t BuLi (4b, c ). The formation of3 demonstrates a novel route to asymmetric heterocyclic 1, 2‐diphosphine ligands. The structure elucidation of the new compounds is based on their 31 P and 13 C NMR data with conclusive chemical shifts and P–C coupling constants, that of the isolated PH‐functionalized diphosphine3 on crystal structure analysis.